Iodometric Determination of Neutral Amino Acids Using Potassium Iodate - Vijayan Ranjitha; Salian Gujaran Shruthi; Rai Nibha; Madavu Lokanatha Rai Kuriya (Journal of New Developments in Chemistry, 2022)
In this work, we have reported a simple, cost effective and reliable method for the determination of neutral α-amino acids iodometrically by making use of potassium iodate. This volumetric method determines amino acids instantly, thereby greatly reduces the time of determination.
Keywords: HIO3